Barbed Ribbon Device for Progressive Tension Closure Reduces Seroma After Breast Reconstruction. Issue 6 (December 2017) - Griner, Devan; Steffen, Caleb M.; Day, Kristopher M.; Brzezienski, Mark A.
Abstract : Purpose: Implant-based breast reconstruction is fraught with complications related to seroma formation. Soft tissue stabilization with progressive tension closure (PTC) has been shown to decrease seroma formation after various procedures but is less suitable for mastectomy flap stabilization. We evaluate the incidence of seroma in breast reconstruction using bioabsorbable barbed ribbon devices (BRDs) as a novel approach to PTC. Methods: We performed a retrospective review of all patients whose mastectomy flaps were stabilized with BRDs. These patients were compared with consecutive patients who underwent mastectomy and reconstruction without progressive tension flap stabilization. Patient demographics and outcomes were recorded, including comorbidities, complications, presence of seroma, and total drain days. Results: In the BRD-PTC group, there were 36 breasts compared with 56 in the nonstabilized control group. There were no significant differences in rate of tobacco use, age, or body mass index. We identified 11 seromas in the control group (19.6%) and none in the intervention group ( P = 0.05). In the PTC group, drains were removed an average of 5 days sooner than those in controls ( P = 0.006). Conclusion: Progressive tension stabilization of mastectomy flaps with BRD significantly reduces seroma formation and the duration for which closed suction drainage is required. Abstract : Supplemental digital content is available in the text.